2009
DOI: 10.1002/pbc.21980
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of transient hyperglycemia during induction chemotherapy for pediatric acute lymphoblastic leukemia

Abstract: The prevalence of TH in this study was higher than previously reported. Overweight, age >or=10 years, and use of native L-asparaginase were significant predictors of TH.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
104
4
8

Year Published

2010
2010
2019
2019

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 84 publications
(127 citation statements)
references
References 22 publications
11
104
4
8
Order By: Relevance
“…A number of studies had confirmed that the age >10-year- old when initially diagnosed was the predilection age of hyperglycemia during the child ALL inductive remission period, and it was also a risk factor towards the ketoacidosis, the incidence of the hyperglycemia group was higher (Roberson et al, 2008;Lowas et al, 2009;Roberson et al, 2009;Sonabend et al, 2009;SpinolaCastro et al, 2009), and thus became the index of poor prognosis in a number of collaborative groups. In this study, the occurrence of hyperglycemia during the inductive chemotherapy did not significantly affect the CR rate of children (compared with the euglycemia group, 86.8% vs 95%, P=0.134), while the prognosis of the hyperglycemia group was poorer, the 5-year overall survival rate was significantly lower than the euglycemia group (83.1±6.3% vs 94.2±2.9%, P=0.014), the 5 -year relapse-free rate was also significantly lower than the euglycemia group (64.1±8.9% vs 88.6±3.8%, P<0.001).…”
Section: Discussionmentioning
confidence: 99%
“…A number of studies had confirmed that the age >10-year- old when initially diagnosed was the predilection age of hyperglycemia during the child ALL inductive remission period, and it was also a risk factor towards the ketoacidosis, the incidence of the hyperglycemia group was higher (Roberson et al, 2008;Lowas et al, 2009;Roberson et al, 2009;Sonabend et al, 2009;SpinolaCastro et al, 2009), and thus became the index of poor prognosis in a number of collaborative groups. In this study, the occurrence of hyperglycemia during the inductive chemotherapy did not significantly affect the CR rate of children (compared with the euglycemia group, 86.8% vs 95%, P=0.134), while the prognosis of the hyperglycemia group was poorer, the 5-year overall survival rate was significantly lower than the euglycemia group (83.1±6.3% vs 94.2±2.9%, P=0.014), the 5 -year relapse-free rate was also significantly lower than the euglycemia group (64.1±8.9% vs 88.6±3.8%, P<0.001).…”
Section: Discussionmentioning
confidence: 99%
“…Hyperglycaemia and insulin resistance are common side effects in both diabetic and non-diabetic patients treated with GCs. Insulin resistance develops in around 30% of cancer patients using GCs, with higher percentages in patient groups receiving continuous high doses [41,42].…”
Section: Glucocorticoidsmentioning
confidence: 99%
“…4,5 Hyperglycemia is a common occurrence in pediatric patients during induction chemotherapy of ALL. [6][7][8] The potential causes may include beta cell dysfunction caused by chemotherapeutic drugs such as L-asparaginase, increased insulin resistance and hepatic gluconeogenesis induced by corticosteroids, or synergistic effects of these medications, given that these pharmacological agents are usually combined during initial induction therapy. 4,5 The spectrum of hyperglycemia can range widely from transient isolated episodes to severe life-threatening complications such as diabetic ketoacidosis or non-ketotic hyperglycemic hyperosmolar syndrome.…”
Section: Introductionmentioning
confidence: 99%